Flexibility in a Stackelberg leadership with differentiated goods - Ferreira, Fernanda A. (2014)
We study the effects of product differentiation in a Stackelberg model with demand uncertainty for the ﬁrst mover. We do an ex-ante and ex-post analysis of the proﬁts of the leader and of the follower ﬁrms in terms of product differentiation and of the demand uncertainty. We show that even with small uncertainty about the demand, the follower ﬁrm can achieve greater proﬁts than the leader, if their products are sufﬁciently differentiated. We also compute the probability of the second ﬁrm having higher proﬁt than the leading ﬁrm, subsequently showing the advantages and disadvantages of being either the leader or the follower ﬁrm.